2016
DOI: 10.1146/annurev-food-041715-033128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pathogen Population Heterogeneity and Stress-Resistant Variants on Food Safety

Abstract: This review elucidates the state-of-the-art knowledge about pathogen population heterogeneity and describes the genotypic and phenotypic analyses of persister subpopulations and stress-resistant variants. The molecular mechanisms underlying the generation of persister phenotypes and genetic variants are identified. Zooming in on Listeria monocytogenes, a comparative whole-genome sequence analysis of wild types and variants that enabled the identification of mutations in variants obtained after a single exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…Persister cells are dormant, non‐dividing state with enhanced capability to survive environmental stresses (Buchanan et al., ; Knudsen, Holch, & Gram, ). It could also contribute to L. monocytogenes protection against cleaning and sanitation in food processing environment (Abee, Koomen, Metselaar, Zwietering, & den Besten, ).…”
Section: Factors Influencing the Antibiotic Resistance Of L Monocytomentioning
confidence: 99%
“…Persister cells are dormant, non‐dividing state with enhanced capability to survive environmental stresses (Buchanan et al., ; Knudsen, Holch, & Gram, ). It could also contribute to L. monocytogenes protection against cleaning and sanitation in food processing environment (Abee, Koomen, Metselaar, Zwietering, & den Besten, ).…”
Section: Factors Influencing the Antibiotic Resistance Of L Monocytomentioning
confidence: 99%
“…The ability of strains to persist in a food-processing environment has been the topic of two reviews (Carpentier andCerf 2011, Ferreira et al 2014), however the reason for persistence remains poorly understood. Persistence of strains in food-processing plants can either be due to genotypic and phenotypic features that facilitate the expression of specific genes and lead to enhanced tolerance towards environmental threats, or to the attachment of bacteria to niches and harbourage sites by chance and subsequent survival due to insufficient cleaning and sanitation procedures (Abee et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is possible that some of our data are not directly applicable to all L. monocytogenes strains. However, in food production plants or natural environments there is always heterogeneity of bacteria and stress-resistant variants can be found ( Abee et al, 2016 ). For example, in general L. monocytogenes serotypes 4 and 1/2 were more susceptible to phages compared to strains in other serotypes, however is was reported that in food production plants within one serotype both, phage susceptible and phage insensitive isolates, can be found ( Vongkamjan et al, 2012 , 2013 ; Fister et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%